Cholinergic Stimulation Prevents the Development of Autoimmune Diabetes: Evidence for the Modulation of Th17 Effector Cells via an IFNγ-Dependent Mechanism - George, Junu A.; Bashir, Ghada; Qureshi, Mohammed M.; Mohamed, Yassir A.; Azzi, Jamil; al-Ramadi, Basel K.; Fernández-Cabezudo, Maria J. (Frontiers in Immunology, 2016)
Type I diabetes (T1D) results from T cell-mediated damage of pancreatic β-cells and loss of insulin production. The cholinergic anti-inflammatory pathway represents a physiological link connecting the central nervous and immune systems via vagus nerve, and functions to control the release of proinflammatory cytokines. Using the multiple-low-dose streptozotocin (MLD-STZ) model to induce experimental autoimmune diabetes, we investigated the potential of regulating the development of hyperglycemia through administration of paraoxon, a highly specific acetylcholinesterase inhibitor (AChEI). We demonstrate that pretreatment with paraoxon prevented hyperglycemia in STZ-treated C57BL/6 mice. This correlated with a reduction in T cell infiltration into pancreatic islets and preservation of the structure and functionality of β-cells. Gene expression analysis of pancreatic tissue revealed that increased peripheral cholinergic activity prevented STZ-mediated loss of insulin production, this being associated with a reduction in IL-1β, IL-6, and IL-17 proinflammatory cytokines. Intracellular cytokine analysis in splenic T cells demonstrated that inhibition of AChE led to a shift in STZ-induced immune response from a predominantly disease-causing IL-17-expressing Th17 cells to IFNγ-positive Th1 cells. Consistent with this conclusion, inhibition of AChE failed to prevent STZ-induced hyperglycemia in IFNγ-deficient mice. Our results provide mechanistic evidence for the prevention of murine T1D by inhibition of AChE and suggest a promising strategy for modulating disease severity.